Trends in Enterococcus faecium Bacteremia: Exploring Risk Factors with Emphasis on Prior Antibiotic Exposure - Erik Sörstedt; Gustaf Ahlbeck; Ulrika Snygg-Martin (Microorganisms)
Enterococcal bacteremia (EB) is on the rise both in Sweden and globally. While Enterococcus faecalis (E. faecalis) is susceptible to ampicillin and piperacillin/tazobactam (pip/taz), Enterococcus faecium (E. faecium) is not. Historically, most enterococcal infections have been caused by E. faecalis, but the epidemiology is changing with increasing recognition of enterococci as nosocomial pathogens and the emergence of resistance to commonly used antimicrobial agents. The use of pip/taz has increased dramatically in Sweden, but it is unknown if this has affected the relative incidence of E. faecalis/E. faecium bacteremia. Here, we investigate whether the number and proportion of E. faecium bacteremia (EfmB) cases have increased. Additionally, risk factors associated with EfmB with a focus on prior antibiotic exposure are analyzed. Medical journals of 360 patients with EB admitted to Sahlgrenska University Hospital are reviewed. The proportion of EfmB cases increased from 41% in 2015 to 51% in 2021. Hospital-acquired infection, previous exposure to pip/taz, and carbapenems are identified as independent risk factors for EfmB. There are considerable patient-related differences between the EfmB and EfsB groups, but there is no difference in mortality rates. In conclusion, the increasing proportion of EfmB cases is concerning and is seen parallel to the expanding use of pip/taz, one possible contributing factor. Our findings suggest that a cautious approach to antibiotic use is essential to prevent the spread of antibiotic-resistant bacteria.